Teacher’s Efforts in Improving Reading Literacy with SI PANCA Extracurricular (Siswa Pandai Membaca) in Elementary School - Galuh Safitri; Sukartono Sukartono (Lectura : Jurnal Pendidikan, 2023)
Education is crucial for everyone because it emphasises the importance of reading literacy, which is a skill that everyone should possess because it can help people learn new things and gain new insights from their previous reading. The aim of this study is to find out the teacher’s efforts in improving reading literacy with the SI PANCA extracurricular (Siswa Pandai Membaca) in classroom. The method used was a qualitative method with a phenomenological design, namely discussing the process and meaning of phenomena as the reality of the subject at Sekolah Dasar (SD) Muhammadiyah Wonorejo. Research data was collected using interviews, observation, and documentation. The points in the interview were efforts to increase reading literacy with SI PANCA, factors that influence SI PANCA, and solutions to overcome SI PANCA constraints. Points of observation included the objectives of SI PANCA, plans to improve reading literacy with SI PANCA, SI PANCA plans that help learning, and materials used in SI PANCA that can support the learning process. The results of this study indicated that the extracurricular SI PANCA programme had a great impact on teaching and learning activities because students become fluent readers and are independent readers of material that previously had to be read by the teacher, as well as an increase in reading literacy skills in students both at school and at home. In conclusion, the extracurricular SI PANCA at SD Muhammadiyah Wonorejo is going well with the progress of students’ abilities.